Desain OPTIMALISASI LAYANAN PEMESANAN MAKANAN ONLINE DI KANTIN KAMPUS MENGGUNAKAN SIMULASI: SEBUAH STUDI KONSEPTUAL - septian, Mohammad Fajar (Jurnal Komputer Bisnis, 2025)
This research conceptually analyzes the optimization of food ordering services in campus canteens through the development of an online system and simulation analysis. Key issues addressed include long queues during peak hours, inefficient order recording, and difficulties in daily sales recapitulation. The proposed system is designed to expedite the ordering process, record transactions, and facilitate menu and stock management. The system design encompasses client-server architecture, Use Case Diagrams, database design, and process flowcharts. UI/UX visualizations were also developed for both user and admin flows. Conceptual simulation analysis indicates that this system has the potential to reduce waiting times, enhance operational efficiency, and optimize canteen resource management. A significant improvement in application quality and user experience is also anticipated.